FXYD2 marks and regulates maturity of β cells via ion channel-mediated signal transduction - Clarissa Tacto; Meghan Tahbaz; Andrew Salib; Shudi Wang; Fritz Cayabyab; Jinhyuk Choi; Kiyoka Kim; Yu Hamba; Harvey Perez; Paul D. Gershon; Robert Damoiseaux; Tae Gyu Oh; et al. (Nature Communications)
Abstract Human pancreatic islets regulate organ development and metabolic homeostasis, with dysfunction leading to diabetes. Human pluripotent stem cells (hPSCs) provide a potential alternative source to cadaveric human pancreatic islets for replacement therapy in diabetes. However, human islet-like organoids (HILOs) generated from hPSCs in vitro often exhibit heterogeneous immature phenotypes such as aberrant gene expression and inadequate insulin secretion in response to glucose. Here we show that FXYD Domain Containing Ion Transport Regulator 2 (FXYD2) marks and regulates functional maturation and heterogeneity of generated HILOs, by controlling the β cell transcriptome necessary for glucose-stimulated insulin secretion (GSIS). Despite its presence in mature β cells, FXYD2 is diminished in hPSC-derived β-like cells. Mechanistically, we find that FXYD2 physically interacts with SRC proto-oncogene, non-receptor tyrosine kinase (SRC) protein to regulate FXYD2-SRC-TEAD1 signaling to modulate β cell transcriptome. We demonstrate that FXYD2High HILOs significantly outperform FXYD2Low counterparts to improve hyperglycemia in STZ-induced diabetic immune deficient mice. These results suggest that FXYD2 marks and regulates human β cell maturation via channel-sensing signal transduction and that it can be used as a selection marker for functional heterogeneity of stem cell derived human islet organoids.